Developing Early Childhood Arithmetic Cognitive Skills in Group B RA Al Istiqomah Through the Traditional Game of Congklak (Universitas Pendidikan Indonesia Kampus Cibiru, 2024)
This study aims to analyze the effect of the traditional game of congklak on the cognitive abilities of early childhood numeracy. The background of the study is that many children aged 5–6 years have difficulty recognizing numbers and understanding basic arithmetic concepts. The research method uses a quantitative approach with a quasi-experimental non-equivalent control group design. The research subjects consisted of an experimental group using congklak in learning and a control group using conventional methods. The research instruments were cognitive tests, observations, and interviews. The results showed a significant increase in the experimental group, with an average score increasing from 66 to 81.33, while the control group only increased from 77.89 to 81.05. The results of the ANCOVA test showed a significant difference (Sig. 0.001) with a Partial Eta Squared value of 0.124. These findings prove that congklak is effective as a fun, interactive learning medium, and is able to improve children's concentration and strategies. In conclusion, the traditional game of congklak can be used as an alternative for numeracy learning in early childhood education while preserving local culture